Testing the role of functional trait expression in plant–plant facilitation. (28th September 2020) - van der Merwe, Stephni; Greve, Michelle; Olivier, Bernard; le Roux, Peter C.
Abstract: Positive biotic interactions between plant species may strongly affect species and community‐level patterns, but the processes through which benefactor species alter the performance of interacting species (via, e.g. beneficial mechanisms like resource provisioning) are still inadequately understood. One poorly explored potential explanation is that plant–plant facilitation could occur through the impact of benefactor species on the functional trait expression of beneficiary species. Indeed, plant species that affect local conditions can modify functional trait expression of interacting species, thereby improving their performance and resulting in a facilitative interaction. However, the response of intraspecific trait variation to biotically driven microhabitat modification, and its role in determining the outcome of plant–plant interactions, has rarely been explored. Here, we test whether growing with benefactor species affects the expression of functional traits of eight species, encompassing different plant growth forms, in two contrasting study systems. This is achieved using a paired sampling approach to compare values of seven functional traits of conspecific individuals growing within and adjacent to cushion plants (i.e. benefactor species which are known to strongly alter microhabitat conditions and to have positive effects on some of the focal species). In addition, we test whether the effect of biotic interactions on functional trait expression changes along elevational gradients, as the outcome of biotic interactions is expected to vary with elevation. Contrary to predictions, in both systems, intraspecific trait variation was not well explained by the biotic interaction with the cushion plant species or the variation in abiotic conditions associated with elevational gradients. Where biotic interactions did affect functional trait expression and bivariate trait relationships, traits responded variably between species, suggesting that context specificity may be a constraint to predicting how intraspecific trait variation responds to plant–plant interactions, adding to the growing body of literature that challenges the generality and predictability of the drivers of intraspecific trait variation. This research, therefore, suggests that benefactor species' facilitative process is likely not through an impact on intraspecific trait expression, and that instead other processes may be more important for translating beneficial microhabitat modification or increased resource availability by benefactor species into positive impacts on beneficiary species. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.